The Distance between Zurich and Todtnauberg - Anderson, A. K. (Religions, 2018)
This paper focuses on two poems written by Paul Celan after first encounters he had with writers who held great significance for him. In 1960 Celan met fellow Jewish poet Nelly Sachs at the Stork Inn in Zurich, and afterwards recorded the event in the poem Zürich, Zum Storchen. Seven years later, Celan visited Martin Heidegger at his hut in the German mountains. Celan's depiction of this encounter is found in the poem Todtnauberg. In this essay, I make a two-fold argument regarding the Zurich poem. First I claim that Todtnauberg is clearly crafted in light of the earlier Sachs text, a fact that has been overlooked by previous scholarship. As such, it is only in placing the two texts side by side that a complete understanding of Todtnauberg comes into view. Second I will indicate how the Zurich poem reflects key elements of an approach to the problem of evil that I term an enestological theodicy. Such a term needed to be coined, since this sort of theodicy does not fit in the more traditional narrative categories related to the problem of evil.